LABORATORY STUDIES OF CHANGES IN THE STRENGTH CHARACTERISTICS OF CONCRETE FOR TRANSPORT AND UNDERGROUND CONSTRUCTION DEPENDING ON STORAGE OF AGGREGATES - Borshchevskyi, S. V. (Science and Transport Progress, 2005)
Are considered a technique and results of experiments spent on concrete samples, on study of change durability of the characteristics of a concrete stone depending on time and conditions of a storage of containing components. By the received results the practical conclusions are made.